Arbuscular mycorrhizal fungi selection for Coffea canephora Pierre ex A. Froehner clonal cultivar conilon ‘BRS OURO PRETO’ - Ardito, Ana Carolina da Silva; Saggin Junior, Orivaldo José; Ortega Fors, Rosalba; Costa, Rogério Sebastião Correa da; Silva, Eliane Maria Ribeiro da (Coffee Science - ISSN 1984-3909, 2017)
Coffee production in Brazil expands to warmer regions with Coffea canephora clonal cultivar Conilon ‘BRS Ouro Preto’. The response of ‘BRS Ouro Preto’ to arbuscular mycorrhizal fungi (AMF) inoculation has not been tested. This research aimed to select AMF species capable of promoting growth and phosphate nutrition of this cultivar. Three clones were evaluated (M057, M194 e M199) in three Ultisols, collected in areas under sugarcane (Soil 1), Cerrado (Soil 2) and Atlantic Forest (Soil 3). The inoculation treatments were: Acaulospora colombiana+Glomus sp., Acaulospora scrobiculata, Claroideoglomus etunicatum+Glomus sp., Dentiscutata heterogama, Gigaspora margarita and Rhizophagus clarus, besides two not inoculated controls, one of them with complete fertilization. The first and third soils promoted greater vegetative plant development. The chlorophyll and phosphorus content in leaves was higher in plants of soil 3. The best response to inoculation, expressed through plant growth and nutrition, was verified in soil 1, with the best treatments being C. etunicatum+ Glomus sp. and G. margarita. The species Glomus sp., present in treatments A. colombiana+ Glomus sp. and C. etunicatum+ Glomus sp., exhibited high sporulation and promoted growth and nutrition of ‘BRS Ouro Preto’. Clones M057 and M194 had the highest growth, response to inoculation and AMF sporulation, compared to clone M199. Clones M057 and M194 can, therefore, be considered mycotrophic, and promoters of AMF sporulation, while clone M199 can be classified as poorly mycotrophic.